2020
DOI: 10.3390/w12102794
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Bubble Collapse Near the Liquid-Liquid Interface

Abstract: Bubble collapse near the liquid–liquid interface was experimentally studied in this paper, and the dynamic evolution of a laser-induced bubble (generation, expansion, and collapse) and the liquid–liquid interface (dent and rebound) were captured by a high-speed shadowgraph system. The effect of the dimensionless distance between the bubble and the interface on the direction of the liquid jet, the direction of bubble migration, and the dynamics of bubble collapse were discussed. The results show that: (1) The j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The dependence of the bubble dynamics on an anisotropy parameter (Supponen et al 2016) was also discussed. A similar bubble jet behaviour was also reported in the work of Yin et al (2020). In the present work, the electric discharge method (Fong et al 2009;Cui et al 2018) is used to generate centimetre-scale cavitation bubbles, which allows us to achieve a higher spatio-temporal resolution of bubble dynamics and interface evolution than in earlier works.…”
Section: Introductionsupporting
confidence: 76%
“…The dependence of the bubble dynamics on an anisotropy parameter (Supponen et al 2016) was also discussed. A similar bubble jet behaviour was also reported in the work of Yin et al (2020). In the present work, the electric discharge method (Fong et al 2009;Cui et al 2018) is used to generate centimetre-scale cavitation bubbles, which allows us to achieve a higher spatio-temporal resolution of bubble dynamics and interface evolution than in earlier works.…”
Section: Introductionsupporting
confidence: 76%
“…micrometer droplets of one liquid in another) produced by ultrasonic cavitation. Despite the complexity and multitude mechanisms implicated in this process [19,20], it is generally accepted that the emulsion is mainly produced by bubble cavitation. Considering that spark ignition in liquid also induces bubble formation with expansionimplosion dynamics [21,22], it may be concluded that under certain conditions, discharges near the interface of two immiscible liquids may lead to emulsion formation.…”
Section: Introductionmentioning
confidence: 99%
“…The unsteady nature of cavitating flows (including the phenomena relevant to the cavitation cloud break-off at the macro-scale as well as bubble collapse at the micro-scale) generates pressure waves that travel throughout the domain [22,23]. These propagating waves will interact with the domain boundaries in different ways (varying from 100% reflection to 100% transmission) depending on the experimental set up.…”
Section: Introductionmentioning
confidence: 99%